Search for evolutionary changes in the periods of cepheids: V1033 Cyg, a classical cepheid at the first crossing of the instability strip - Berdnikov, L. N.; Pastukhova, E. N.; Kovtyukh, V. V.; Lemasle, Bertrand; Kniazev, A. Yu.; Usenko, I. A.; Bono, G.; Grebel, Eva K.; Hajdu, Gergely; Zhuiko, S. V.; Udovichenko, S. N.; Keir, L. E. (Astronomy letters, 2019)
For the classical Cepheid V1033 Cyg we have constructed an O—C diagram spanning a time interval of 117 years. The O—C diagram has the shape of a parabola, which has made it possible to determine for the first time the quadratic light elements and to calculate the rate of evolutionary increase in the period dP/dt = 18.19 (±0.08) syr−1, in agreement with the results of theoretical calculations for the first crossing of the instability strip. Thus, V1033 Cyg is the second actually observed Cepheid (after α UMi) that crosses the instability strip for the first time.